Islamic Social Instruments and Sustainable Development Goals (SDGs) Framework - Rusydiana, Aam Slamet; Khalifah, Mohamad Handi (Management and Sustainability, 2023)
This research will try to measure the priority scale of several Islamic social instruments within the framework of the Sustainable Development Goals. This is also a form of the contribution of Islam towards the realization of the Sustainable Development Goals, so that it will not only act as a solution in alleviating poverty and income distribution, but also become one of the global instruments collected in the Development Goals Global Sustainability. This research shows that the Sustainable Development Goals criteria that are most relevant to the Islamic philanthropy framework that emerged in order are: 1) Social Development, 2) Economic Development, 3) Inclusive Development, and 4) Environment Development. Meanwhile, in the context of alternative Islamic social instruments, the research highlights that the most relevant to the 17 points of the Sustainable Development Goals (SDGs) include: 1) Waqf, 2) Islamic Micro Financing, 3) Zakah, and 4) Islamic Micro Insurance.